Application of Dynamic Stochastic General Equilibrium model in forecasting economic growth of Ho Chi Minh City - Le , Hoàng Anh; Le , Chí Hùng; Nguyen , Thị Phương Trinh (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study aims to develop and apply the Dynamic Stochastic General Equilibrium (DSGE) model to forecast the economic growth of Ho Chi Minh City, a key economic hub in Vietnam. The study utilizes time series data from Q4 2011 to Q4 2023, including macroeconomic variables such as interest rates, inflation, investment, consumption, GRDP growth, and external economic influences. Based on this dataset, the authors estimate and test the stationarity of variables using the Dickey-Fuller method while employing the DSGE model to analyze the impact of economic shocks on Ho Chi Minh City’s growth. The results indicate that the DSGE model effectively captures economic fluctuations and reflects the influence of macroeconomic shocks and policy adjustments on GRDP growth. Furthermore, the model forecasts a positive growth trend for Ho Chi Minh City in 2024, with an expected increase exceeding 6%. These findings provide a scientific basis for policymakers to develop sustainable economic growth strategies at the local level.